Condiciones necesarias y suficientes de una correspondencia hemicontinua - Carranza Calderón, Federico (2014)
Applications that take vectors sets are studied, called correspondences.We analyze the concept of continuity for correspondences, based on the upper and lower hemicontinuity, then get a sequential characterization of hemicontinuas correspondence.